2002
DOI: 10.1021/ma020895v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding Effects on the Dynamic Swelling of P(N-iPAAm-co-MAA) Copolymers. A Case of Autocatalytic Swelling Kinetics

Abstract: The swelling kinetics of a series of P(N-iPAAm-co-MAA) copolymers and their P(N-iPAAm) and P(MAA) homopolymers previously soaked under different acidic and neutral conditions have been studied at pH 7 to probe the hydrogen-bonding ability of comonomers. Experimental data analysis has revealed that although the state due to the previous soaking pH does not exert any influence on the equilibrium swelling value of copolymers, it exerts a strong influence on their swelling kinetics. Copolymers gels ranging in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 24 publications
3
61
0
Order By: Relevance
“…These results suggest that Schott , s second-order kinetic equation is adequate to describe the whole swelling process of chitosan hydrogel membranes in buffer solutions. Our results are consistent with the statements of others that the swelling kinetics behaviour of ionic hydrogels (anionic and cationic hydrogels) is in good accordance with Schott , s second-order diffusion kinetics [49][50][51][52][53][54][55]. Table 2 shows that values of apparent swelling rate constant for Ch/GA and Ch/GA/SA membranes are of the same order of magnitude for acidic and neutral swelling media but they increase for alkaline solutions.…”
Section: Case III (Or Anomalous Diffusion Non-fickian Diffusion)supporting
confidence: 92%
“…These results suggest that Schott , s second-order kinetic equation is adequate to describe the whole swelling process of chitosan hydrogel membranes in buffer solutions. Our results are consistent with the statements of others that the swelling kinetics behaviour of ionic hydrogels (anionic and cationic hydrogels) is in good accordance with Schott , s second-order diffusion kinetics [49][50][51][52][53][54][55]. Table 2 shows that values of apparent swelling rate constant for Ch/GA and Ch/GA/SA membranes are of the same order of magnitude for acidic and neutral swelling media but they increase for alkaline solutions.…”
Section: Case III (Or Anomalous Diffusion Non-fickian Diffusion)supporting
confidence: 92%
“…It can be observed that almost all of the experimental points lie on the respective straight lines for each hydrogel. However, the values did not fit the straight lines in the first few minutes, suggesting a different kinetics order, probably a first-order process, as suggested by Diez-Peña et al 35 A new plot (not shown) was obtained without the initial points and a better fit and linear correlation coefficients (R 2 ) were observed. The R 2 value for the straight line for Pam-Ac increases from 0.9992 to 0.9995.…”
Section: Swelling Kineticsmentioning
confidence: 65%
“…In general, the swelling follows a first-order or a secondorder kinetics. 35 The second-order rates may be obtained from the well-known equation…”
Section: Swelling Kineticsmentioning
confidence: 99%
“…24,25 Copolymer composition (Table 1) was determined by elemental analysis performed using a CHN EA 1108-elemental analyzer (Carlo Erba Instruments, Milano, Italy). Because the previous swelling history was shown to have strong influence on the swelling behavior, 26 samples from synthesis were soaked under acidic medium (pH 1.2) and dried in a vacuum oven at 60°C for 24 hours in order to obtain homogeneous samples with a controlled morphology history.…”
Section: Synthesis Of Homopolymers and Copolymer Hydrogelsmentioning
confidence: 99%
“…10,[16][17][18][19][20][21][22][23][24][25][26] These copolymers possess a wide range of swelling characteristics depending on composition and previous swelling history, [24][25][26] which potentially allow hydrogels to be obtained for specific uses. Because of the N-iPAAm moiety, these copolymers are able to respond to temperature changes, while the ionizable carboxyl group provides pH sensitivity.…”
Section: Introductionmentioning
confidence: 99%